TUGAS DAN FUNGSI KEPALA DESA BESERTA PERANGKAT DESA DALAM MENINGKATKAN KINERJA PADA KANTOR DESA NAMO BINTANG KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Sri Ulina (Universitas Medan Area, 2015)
The village administration is the smallest unit in the structures of local government, the village government has its own duties and authorities as stipulated by Law. The main substance that has not changed is that the village government as the government administration at the village level. The purpose of this study to see how the duties and functions of the village head and village in improving performance at the village office Namo Binang Pancur Batu Subdistrict of Deli Serdang. This type of research is qualitative descriptive method. Source of data derived from interviews san documentation. The results showed under the implementation of the basic tasks and functions of the village and the village is conducted in accordance with the provisions of the legislation in force. On the implementation side than the basic tasks and functions in each village needs to be supported with human resources (HR) and adequate infrastructure in order to achieve the tasks and services to the public.